Implications of the Non-Involvement of the Cek Bocek Selesek Reen Sury Indigenous Community in the Mining Business Approval Process in Sumbawa Regency - Ari Ade Kamula (Perantara Law Review, 2024)
This research discusses the implications of not involving the Cek Bocek Salesek Reen Sury indigenous community in the mining business approval process in Sumbawa Regency. This research aims to explore the form of legal protection for indigenous peoples who were not involved in the approval. The method used is a socio-legal approach with qualitative analysis based on primary, secondary and tertiary data. The results show that the exclusion of indigenous peoples violates the principles of participation, transparency and accountability as stipulated in the Mineral and Coal Mining Law and the Environmental Management Law. In addition, it ignores the principles of sustainable development, which should prioritize a balance between economic, social and environmental interests. Sociologically, this has led to prolonged conflicts between companies and indigenous communities, which include social tensions and decreased community access to their customary lands. In conclusion, the involvement of indigenous peoples in mining business approvals is essential to ensure equitable legal protection, maintain social harmony, and avoid negative impacts that have the potential to damage relations between indigenous peoples and the government and companies. Strategic recommendations are needed to create more inclusive governance in the mining licensing process.